2014
DOI: 10.1177/193758671400700405
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Windows and Daylight on Acute-Care Nurses' Physiological, Psychological, and Behavioral Health

Abstract: Critical care/intensive care, lighting, nursing, quality care, work environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
77
1
5

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 50 publications
6
77
1
5
Order By: Relevance
“…The positive effects of biophilic interventions on blood pressure and heart rate are consistent with previous studies on the health benefits of windows and daylight, indoor green plants, and wooden environments. 32,61,62 Interestingly, those results were also consistent with a recent meta-analysis summarizing the health benefits of outdoor nature, which showed increased green space exposure was associated with significant decreases in diastolic blood pressure and heart rate. 16 We found increased RMSSD, although not statistically significant, in both the natural elements and combination conditions.…”
Section: Physiological Stress Levelsupporting
confidence: 86%
“…The positive effects of biophilic interventions on blood pressure and heart rate are consistent with previous studies on the health benefits of windows and daylight, indoor green plants, and wooden environments. 32,61,62 Interestingly, those results were also consistent with a recent meta-analysis summarizing the health benefits of outdoor nature, which showed increased green space exposure was associated with significant decreases in diastolic blood pressure and heart rate. 16 We found increased RMSSD, although not statistically significant, in both the natural elements and combination conditions.…”
Section: Physiological Stress Levelsupporting
confidence: 86%
“…The SEIPS model acknowledges that the nurse work system is comprised of individuals and their interactions with the environment, tasks, tools and technology, and the larger organisation through policies and regulations (Carayon et al, ; Holden et al, ). As part of the nurse work system, the physical health care environment (PHE) has been identified as impacting nurse fatigue through environmental variables including unit, breakroom and patient room layouts, lighting, noise, temperature and supply locations (Nejati, Shepley, Rodiek, Lee, & Varni, ; Steege et al, ; Steege et al, ; Zadeh, Shepley, Williams, & Chung, ).…”
Section: Contributing Factors To Nurse Fatiguementioning
confidence: 99%
“…Prior research has largely focused on design elements related to noise, temperature and lighting in regard to nurse fatigue (Steege et al, ; Zadeh et al, ). Specifically, Zadeh et al () found nurses who were exposed to daylight at their workstation exhibited significantly improved physiological (blood pressure and body temperature) and psychological (behavioural indicators of sleepiness, mood, frequency of communication and positive social interaction) responses, suggesting access to daylight can positively impact nurses and help reduce nurse fatigue in the physical, emotional and psychosocial dimensions. Participants in this study identified sensory factors as impacting all four fatigue dimensions.…”
Section: Impact Of the Phementioning
confidence: 99%
See 2 more Smart Citations